Philosophical Study: As a Form of Students' Understanding of Pancasila Education - Peggy Dian Septi Nur Angraini; Sekar Revianti Prawita; Verorosa Enjel Helentahta; Anandra Fitra Nabil; Audiva Jelita Anjani; Khoirunnisa Latifah; Rafiq Adi Wardana (Global Journal of Law, AI & Ethics, 2025)
Philosophical Study: As a Form of Students' Understanding of Pancasila Education Philosophy and Pancasila Education are important topics aimed at discovering the role of philosophy in Pancasila Education and students' efforts to understand philosophy. A comprehensive literature research method is used to abstract the essence with relevant and appropriate norms related to and in accordance with philosophical studies, reflecting students' understanding of Pancasila Education. The philosophical aspects that help in learning Pancasila Education are ontology, epistemology, and axiology. Ontology helps in understanding the existence of truth in Pancasila, epistemology helps in providing an impetus for a deep understanding of the truth of Pancasila to be realized in daily life, and axiology helps in understanding the benefits of Pancasila values. Philosophizing allows students to understand and apply various perspectives in appreciating diversity, developing attitudes, openness, and tolerance toward all social changes. Beside, philosophy can actually be easily understood in life because it is always related to philosophy. Students should also strive to understand Pancasila Education thru philosophy because it is only right that students are able to think critically in higher education. Thus, it helps in solving problems and making decisions according to the current conditions, based on truth